HUMANIZAÇÃO DO ESPAÇO CARCERÁRIO: UMA ANÁLISE DAS POLÍTICAS PÚBLICAS PARA OFERTA DE TRABALHO E EDUCAÇÃO NO SISTEMA PRISIONAL DE MINAS GERAIS | Humanization of prison space: an analysis of public policies for labor and education in the prison system of Minas Gerais (Trabalho & Educação, 2018)
The present work was extracted from the master's research carried out at the Faculty of Education of the Federal University of Minas Gerais (2015/2017). The research entitled "Humanization of prison space: an analysis of public policies for labor and education in the prison system of Minas Gerais" tried to answer the following question: Why is the rate of access to labor and education in the prison system is still so low? Minas Gerais has the second largest prison population in Brazil with approximately 60,000 people incarcerated. In 2016, the percentage of prisoners in the prison system in Minas Gerais who had not completed elementary school was 65.89% and only 12.11% of those incarcerated had access to educational activities. The research sought to analyze the execution of the public policies directed at the right to labor and education to the custodial prisoners of Minas Gerais. Although our Constitution establishes Brazil as a State of Law, what is seen in criminal execution is a cruel and dramatic situation with practices that are in conflict with the Constitution and with the Law. The sentenced person is not treated as a subject with rights, his fundamental rights are violated by the omission of the State that does not establish the necessary public policies for the preservation of their human dignity. The theoretical framework was used to analyze the identified power relations and to compare the established normative standard (according to which all prisoners have the right to labor and education) and the reality observed in the prison system. The analysis carried out in this study had as premise that labor and education are rights of all sentenced and not favors granted only to those who demonstrate merit. In order to justify the importance of labor in the formation of the subject who is serving a sentence of deprivation of liberty, we have recourse to Karl Marx, considering the class struggle as the motor of history and labor in its formative and transforming dimension, as an educational principle. Foucault's contribution had fundamental importance to explain the genesis, development and function of the prison, which since its inception has been used as an instrument of control, discipline and power. Fernández Enguita helped to understand the school as a scenario where a series of material social practices occurs, in addition to the transmission and circulation of ideas. We also resorted to Thompson's discussions and questions about the difficulty of reconciling the functions of the sentence established by law, and to Saviani's careful exposition of the history of the relationship between labor and education. There are contributions from several other authors who defended ideas related to the problem discussed in the research and which were fundamental for the reflections proposed in the study. As research methodology was used the research processes of quantitative and qualitative approaches. The process comprised document analysis, participant observation and questionnaire. The greatest difficulty encountered during the survey was access to data. For this reason, it was necessary to resort to several sources and, later, to integrate the data received from each one of them. The triangulation of data was the strategy used to increase the quality of the research. The data analyzed revealed that the higher the number of custodial inmates in a prison unit, the lower the percentage of educational attendance in this unit. The percentage of educational attendance above 40% was only reached in units that housed less than 200 people in custody. Still in relation to this indicator when the variable is the labor supply, the same relation was observed, that is, the higher the number of prisoners in the prison unit, the lower the percentage of access to labor activities. The comparative analysis of data from the three models of prison management (traditional public model, administered by SEAP - State Department of Prison Administration, the private model administered by APAC - Association for the Protection and Assistance of Convicted Persons, and the model established by Public Private Partnership - PPP, administered by GPA - Associated Prison Managers) shows that the percentages of both education and work in the GPA / PPP model were closer to the public system of SEAP than to the APAC system, proving that the state's bet in this new model of prison management system does not serve the public interest, especially with regard to the social integration function of the sentence. The architectural model used by the State and the GPA in the construction of prison units prioritizes safety, not humanization. While in APAC there are spaces of free circulation with gardens and areas of social coexistence, in the public units of SEAP and in the units of the GPA there are many grids and almost no space of social coexistence. While APAC values trust and solidarity, SEAP and the GPA are concerned with overruling all the autonomy of the subjects deprived of their liberty. A closer look at the GPA complex will show that a new power laboratory comes into action under the title of modern prison, at a time when there has been an exacerbation of sentences and a process of mass incarceration in Brazil. This new prison model should raise a great deal of concern, as a form never seen in Brazil for the exploitation of criminal execution as a lucrative activity is taking shape.___O presente trabalho foi extraído da pesquisa de mestrado realizada na Faculdade de Educação da Universidade Federal de Minas Gerais (2015/2017). A pesquisa intitulada “Humanização do espaço carcerário: Uma análise das políticas públicas para oferta de trabalho e educação no sistema prisional de Minas Gerais” tentou responder à seguinte questão: Por que ainda é tão baixo o índice de acesso ao trabalho e educação no sistema prisional? Minas Gerais tem a segunda maior população carcerária do Brasil com aproximadamente 60.000 pessoas presas. Em 2016, o percentual de custodiados do sistema prisional de Minas Gerais que não havia completado o ensino fundamental era de 65,89% e apenas 12,11% tinham acesso a atividades educacionais. A pesquisa buscou analisar a execução das políticas públicas direcionadas à oferta do direito ao trabalho e à educação aos custodiados do sistema prisional do estado de Minas Gerais.  Apesar da Constituição da República estabelecer o Brasil como um Estado de Direito, o que se assiste na execução penal é uma situação cruel e dramática com práticas que se mostram em conflito com a Constituição e com a Lei. O sentenciado não é tratado como sujeito de direitos, seus direitos fundamentais são violados pela omissão do Estado que não estabelece as necessárias políticas públicas para que seja preservada a sua dignidade humana. Recorreu-se ao referencial teórico para analisar as relações de poder identificadas e comparar o padrão normativo instituído (segundo o qual todos os presos têm direito ao acesso ao trabalho e à educação) e a realidade observada no sistema prisional. A análise realizada neste estudo teve como premissa que trabalho e educação são direitos de todos os sentenciados e não favores concedidos somente a quem demonstre merecimento. Para fundamentar a importância do trabalho na formação do sujeito que cumpre pena privativa de liberdade se recorreu ao pensamento de Karl Marx, considerando a luta de classes como o motor da história e o trabalho em sua dimensão formadora e transformadora, como princípio educativo. A contribuição de Foucault foi de fundamental importância para explicar a gênese, o desenvolvimento e a função da prisão, que desde sua criação tem sido utilizada como instrumento de controle, disciplina e poder. Fernández Enguita ajudou a compreender a escola como um cenário onde ocorre uma série de práticas sociais materiais, para além da transmissão e circulação de ideias. Recorreu-se, ainda, às discussões e questionamentos de Thompson sobre a dificuldade de se conciliar as funções da pena estabelecidas pela lei, e à criteriosa exposição de Saviani para descortinar a história da relação entre trabalho e educação. Várias são as contribuições de diversos outros autores que defenderam ideias relacionadas ao problema discutido na pesquisa e que foram de fundamental importância para as reflexões propostas no estudo. Como metodologia de pesquisa utilizou-se os processos de investigação de abordagens quantitativa e qualitativa. O processo compreendeu a análise de documentos, a observação participante e o questionário. A maior dificuldade encontrada durante a pesquisa foi o acesso aos dados. Por essa razão, foi preciso recorrer a diversas fontes de informações e, posteriormente, fazer a integração dos dados recebidos de cada uma delas. A triangulação de dados foi a estratégia utilizada visando a ampliação da qualidade da pesquisa. Os dados analisados revelaram que quanto maior o número de custodiados existente em uma unidade prisional, menor o percentual de atendimento educacional nessa unidade. O percentual de atendimento educacional acima de 40% só foi atingido em unidades que abrigavam menos de 200 custodiados.  Ainda em relação a esse indicador quando a variável é a oferta de trabalho, observou-se a mesma relação, ou seja, quanto maior o número de custodiados na unidade prisional, menor o percentual de acesso às atividades laborais. A análise comparativa dos dados dos três modelos de gestão prisional (modelo tradicional público, administrado pela SEAP- Secretaria Estadual de Administração Prisional; o modelo privado, administrado pela APAC - Associação de Proteção e Assistência aos Condenados; e o modelo estabelecido por Parceria Público Privada – PPP, administrado pela GPA – Gestores Prisionais Associados) mostra que os percentuais de atendimento tanto de educação como de trabalho no modelo da GPA/PPP se aproximaram mais do sistema público da SEAP do que do sistema da APAC, comprovando que a aposta do estado nesse novo modelo de sistema de gestão prisional não atende ao interesse público, principalmente no que diz respeito à função de integração social da pena. O modelo arquitetônico utilizado pelo Estado e pela GPA na construção das unidades prisionais prioriza a segurança e não a humanização. Enquanto na APAC há espaços de livre circulação com jardins e áreas de convivência social, nas unidades públicas da SEAP e nas unidades da GPA há muitas grades e quase nenhum espaço de convivência social. Enquanto a APAC valoriza as relações de confiança e solidariedade, a SEAP e a GPA se preocupam em anular toda a autonomia dos sujeitos privados de liberdade. Um olhar mais criterioso para o complexo da GPA irá aferir que um novo laboratório de poder entra em ação sob o título de prisão moderna, nesse momento histórico em que tem ocorrido uma exacerbação das penas e um processo de encarceramento em massa no Brasil. Esse novo modelo de prisão deve suscitar uma grande preocupação, pois está entrando em cena uma forma nunca vista no Brasil de exploração da execução penal como atividade lucrativa.